The Effects of Nosema apis and Nosema ceranae Infection on Survival and Phenoloxidase Gene Expression in Galleria mellonella (Lepidoptera: Galleriidae) Compared to Apis mellifera - Erkay Özgör (Insects, 2021)
The study aims to prove the possibility of colonization of N. apis and N. ceranae to the intestine of the greater wax moth, detect the differences of greater wax moth based on the presence of Nosema species and examine the effect of Nosema species on the phenoloxidase level of greater wax moth compared with honeybees. Each group was fed on the 1st day of the experiment with its appropriate diet containing 106 Nosema spores per insect. Each group was checked daily, and dead insects were counted. Furthermore, changes in the level of expression of the phenoloxidase-related gene after Nosema spp. treatment on the 6th, 9th and 12th days, which was detected by Q-PCR, and the mRNA level of phenoloxidase gene were measured in all experiment groups with the CFX Connect Real-Time PCR Detection System. This study shows that Apis mellifera L. has a 66.7% mortality rate in mixed Nosema infections, a 50% mortality rate in N. ceranae infection, a 40% mortality rate in N. apis infection, while there is no death in G. mellonella. A significant difference was found in the mixed Nosema infection group compared to the single Nosema infection groups by means of A. mellifera and G. mellonella (Duncan, p < 0.05). G. mellonella histopathology also shows that Nosema spores multiply in the epithelial cells of greater wax moth without causing any death. The increase in the mRNA level of Phenoloxidase gene in A. mellifera was detected (Kruskal–Wallis, p < 0.05), while the mRNA level of the Phenoloxidase gene did not change in G. mellonella (Kruskal–Wallis, p > 0.05). These findings prove that the Nosema species can colonize into the greater wax moth, which contributes to the dissemination of these Nosema species between beehives.